Effect of Service Quality on Customer Satisfaction in Capture Sight Pho¬to¬¬graphy - Christopher Gian Putra Wijaya (Jurnal Strategi Pemasaran, 2019)
Analysis Effect of service quality on customer satisfaction at Capture Sight Photography Surabaya with Customer Satisfaction as Intervening Variables.There are cultural changes where both men and women especially in big cities are busy working. This has led to the rapid development of the Photography Business. With the start of the many photography businesses that emerged, giving many choices for consumers to visit and photography is used to capture important moments in the lives of consumers.This research was conducted to analyze the influence of Variable Service Quality on Customer Loyalty Consumer Capture Sight Photography in Surabaya with Customer Satisfaction as an Intervening Variable. This study used a 54 customer-distributed questionnaire that had been a consumer of Surabaya Capture Sight Photography at least once in the past six months making its own payments. The questionnaire in this study was formed using a Likert scale questionnaire format. This study uses the partial least square (PLS) analysis technique.